Diagnóstico do aquífero livre da zona norte do Município de Aracaju, Sergipe, através avaliação de parâmetros físico-químicos e biológicos em amostras de água de poços raso - Oliveira, Nathália Krissi Novaes (2016)
Groundwater is large percentage of sweet easily accessible water, and are often the only options for drinking water supply. In general, it have better quality due to interactions with the ground during percolation. In urban areas, however, various activities can compromise the quality and demand of this resource, such as installation of septic tank, wastewater without treatment or with inadequate treatment, improper disposal of solid waste, waterproofing recharge areas, storage of hazardous products underground or overhead tanks without sump, among others. The objective of this study was to evaluate the contamination of free aquifer in north zone of Aracaju/SE, through the analysis of physical, chemical and biological parameters of water samples from shallow wells, related to human activities and potential sources of contamination, and comparing with the limits for drinking water established by Decree N. 2,914/2011 of the Ministry of Health. Samples were collected in two campaigns, evaluating the effects of seasonality. The results showed that all samples were unfit for human consumption, at least two of the 39 analyzed parameters, and more significant changes in the dry period in most parameters. The concentrations of turbidity, nitrite, sodium, sulfate, fluoride, chloride, aluminum, barium, copper, iron, nickel and zinc did not exceed the limits for drinking water in the samples analyzed. Only free residual chlorine, cobalt and chromium were not detected in any of the studied points. The detection of toxic compounds such as benzene, toluene, ethylbenzene and xylene reveal a critical setting, and shows that more attention should be given to these parameters in potable for human consumption assessments.